Customer and competitor orientation on coffee export marketing performance in Central Java: The role of learning organization and entrepreneurial orientation - Sulistya Sulistya; Rohwiyati Rohwiyati; Kusumaningdiah Retno Setiorini (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This research aimed to examine market performance through the two dimensions of customer and competitor orientation. The mediating role of learning organization was examined in the correlation of customer with competitor orientation and coffee export marketing performance in Central Java MSMEs. Furthermore, the moderating role of entrepreneurial orientation was analyzed in the learning organization impact on export marketing performance. The sample consisted of 116 coffee-exporting MSMEs in the Central Java region, Indonesia, selected based on specified criteria. Our data analysis used PLS-SEM (Partial Least Squares–Structural Equation Modeling) to examine the connections between variables. Our findings revealed that 1) customer orientation and learning organization significantly affect export marketing performance, 2) competitor orientation do not significantly affect export marketing performance, 3) Customer and competitor orientation had significant and indirect impact on learning organization and export marketing performance, respectively, and 4) Entrepreneurial orientation moderated the influence of learning organization on export marketing performance.